Interference Design and Numerical Analysis of the Large Pump Gearbox Output Shaft - Tan Yonghu; Yang Changhui (Jixie chuandong)
With respect to the design calculation of the interference fit construction of the output shaft of cooling water pumps used in a nuclear power plant,the design calculation and checking are carried out by using standard formulas and numerical methods specified in the National Standards for limit and interference fit.The contact pressures at the maximum and minimum interference are obtained respectively,and the assessment of the reliability of transmitted torque and material is conducted,then the minimum temperature required for interference assembly is calculated,the protection for the safe and reliable operation of pump is provided.